Pendidikan Islam Berbasis Al-Fatihah: Menanamkan Keimanan, Ibadah dan Akhlak Mulia - Basori Basori; Aisha Barokah; Elis Setiawati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic education is not only aimed at transferring knowledge, but also at forming a complete human being through the development of spiritual, intellectual, and moral aspects. Surah Al-Fatihah as the opening of the Qur'an contains educational values ​​that are very relevant to be used as a foundation in forming human awareness of Allah in the educational process. This article examines the concept of Islamic education through three main terms, namely at-tarbiyah, at-ta'lim, and at-ta'dib, and identifies educational values ​​in Surah Al-Fatihah such as the values ​​of faith, worship, sharia, and stories as instruments of character formation. In addition, the discussion focuses on the role of Surah Al-Fatihah in building the spiritual awareness of students and strengthening the vertical relationship with Allah SWT. The results of the study show that Surah Al-Fatihah is not only a ritual reading, but also an integrative and applicable framework of values ​​in Islamic education. By making this Surah the foundation of learning, the educational process can be directed to produce perfect human beings who are not only intellectually intelligent, but also spiritually strong and have noble morals.